Structure existence areas for complex oxides of perovskite-like structural families - G. A. Geguzina; I. G. Popova (Journal of Advanced Dielectrics, 2025)
Constructed existence areas of different oxygen–octahedral structures of complex oxides are considered and compared. They are found on numerous facts of certain complex oxide compositions of three different structure types: successful and not-so-successful syntheses, on the one hand, and their interatomic bond characteristics calculation and analysis — on the other hand. Developed procedures of the crystal structure detailing the theoretical definition for every oxygen–octahedral structure and its constructing existence areas are shown. By using every structure existence area, one may predict the possibility of the specified complex oxides crystallization in the corresponding structure type.